Multi-objective Planning of the Economic Operation of Microgrid Considering the Energy Loss and the Start-up Cost of Conventional Units - Ke, Xue; Yin, Yiheng; Xu, Zecheng (Journal of physics. Conference series, 2021)
The fluctuation of load and new energy will have an important impact on the operation mode of microgrid. In order to balance the economy and reliability of microgrid, a chance constrained model of microgrid is established firstly. Based on the reliability cost, the operation cost of microgrid under different confidence levels is calculated, and a reasonable confidence level of rotating reserve is obtained. This paper analyzes the impact of energy storage charge and discharge loss and conventional unit start-up cost on the economic operation of the isolated micro grid; for the grid connected micro grid, the economy of its own operation and the effect of auxiliary large grid peak load shedding are taken as the objective function, and the multi-objective programming method proposed in this paper is used to solve the problem. The example analysis shows that the multi-objective programming method in this paper, by combining with particle swarm optimization algorithm, can optimize the weight of different objectives reasonably, which can not only help the large power grid to cut peak and fill valley, but also realize the economy of microgrid operation.